Road Climatology: Determination of Calculated Values of Meteorological Characteristics - Ivan Leonovich; Donatas Čygas (The Baltic Journal of Road and Bridge Engineering)
Practically all the road-related questions are solved with the consideration of climatic factors. Besides, the meteorological characteristics of the region, where the road objects are located, are taken into account, as well as their calculated values. This paper describes a methodology for determining these values. The examples are given on how to calculate the main meteorological characteristics of the percentage of integral probability, which are used in designing, constructing and maintaining roads.